دراسة االستقرارية لبعض معقدات قواعد شف المشتقة من 3 -ميثوكسي-4-هيدروكسي بنزالديهايد مع بعض االيونات الفلزية - الطائي عبد الرحمن خضير عبدالحسين; الطائي عبد الرحمن خضير عبدالحسين; ياقو داني منصور; داود غسان سعدون (Al-Nahrain Journal of Science, 2018)
The idea of research is adapted, five type of aromatic Schiff bases were seleceted and their complexes with divallent Nickel